2007
DOI: 10.1002/hep.21586
|View full text |Cite
|
Sign up to set email alerts
|

Value of the critical flicker frequency in patients with minimal hepatic encephalopathy†

Abstract: Minimal hepatic encephalopathy (MHE) is mainly diagnosed using psychometric tests such as the psychometric hepatic encephalopathy score (PHES). Despite the clinical and social relevance of MHE, psychometric testing is not widespread in routine clinical care. We assessed the usefulness of the critical flicker frequency (CFF), for the diagnosis of MHE and for the prediction of the development of overt episodes of HE. The normal range of PHES in the Spanish population was evaluated in a control group. Subsequentl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
278
4
3

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 288 publications
(296 citation statements)
references
References 150 publications
(174 reference statements)
11
278
4
3
Order By: Relevance
“…7,10,12,[16][17][18] MHE predicts the development of overt HE and also adversely affects survival as shown by several studies. 7,10,18,[84][85][86][87] Das et al 10 studied the progression of MHE to overt HE in relation to severity of liver dysfunction and found that overt HE were more frequent in patients with MHE and Child-Turcotte-Pugh (CTP) score >6. Hartmann et al 7 found that survival was determined only by CTP score irrespective of presence or absence of MHE.…”
Section: Natural History and Survival In Minimal Hepatic Encephalopathymentioning
confidence: 99%
“…7,10,12,[16][17][18] MHE predicts the development of overt HE and also adversely affects survival as shown by several studies. 7,10,18,[84][85][86][87] Das et al 10 studied the progression of MHE to overt HE in relation to severity of liver dysfunction and found that overt HE were more frequent in patients with MHE and Child-Turcotte-Pugh (CTP) score >6. Hartmann et al 7 found that survival was determined only by CTP score irrespective of presence or absence of MHE.…”
Section: Natural History and Survival In Minimal Hepatic Encephalopathymentioning
confidence: 99%
“…20,21 Furthermore, MHE is of prognostic significance as it is a risk factor for the development of overt HE 20,[22][23][24][25] and death. 20,26 Recognizing MHE is important because its treatment can improve cognitive functions [27][28][29][30][31] and quality of life, [27][28][29]31,32 and avert progression to overt HE.…”
Section: 9mentioning
confidence: 99%
“…1 The psychometric hepatic encephalopathy score (PHES), which measures multiple domains of cognitive function, is a reliable test battery for the assessment of cognitive impairment in patients with MHE. 1,2,[11][12][13][14] The inhibitory control test (ICT) is a computerized test of attention and response inhibition that has been used to characterize attention deficit disorder, schizophrenia, and traumatic brain injury. [15][16][17][18] The ICT has recently been added to the list of tests for the diagnosis of MHE.…”
mentioning
confidence: 99%